Peran Website dalam Meningkatkan Daya Saing UMKM Etika Jaya Makmur Desa Benowo - Samudro, Firmansyah Putra; Dermawan, Rizky (Ikatan Da'i Indonesia, 2025)
Etika Jaya Makmur, a micro, small, and medium enterprise (MSME) located in Benowo Village, Surabaya, faces challenges in expanding the market for its leather shoes due to the continued use of traditional marketing methods. A major obstacle is the lack of knowledge among MSME owners about digital marketing, which hinders the optimization of product promotion. This study aims to enhance the competitiveness and market reach of the MSME by introducing and utilizing information technology, specifically through the development of a website as a digital marketing platform. The methods employed include observation, socialization, discussions, and hands-on training sessions. The results of this activity show an increase in the MSME owners' understanding of digital marketing strategies and their skills in creating and managing a website. The developed website serves as a promotional tool that enables the MSME's products to reach a wider range of consumers, unrestricted by distance and time.